Alteration of Bone Turnover Markers in Canonical Wingless Pathway in Patients With Ankylosing Spondylitis - Jinxian HUANG,; Guoxiang SONG,; Zhihua YIN,; Zhongchao FU,; Zhizhong YE, (Archives of Rheumatology, 2016)
Objectives: This study aims to determine the levels of bone turnover markers in canonical wingless pathway in patients with ankylosing spondylitis (AS) and the correlation with disease activity indexes. Patients and methods: We recruited a total of 43 AS patients (34 males, 8 females; mean age 36.8±9.3 years; range 22 to 62 years) and age- and sex-matched 42 healthy controls (32 males, 10 females; mean age 36.1±9.7; range 24 to 59 years). Serum levels of components of canonical wingless pathway including Dickkopf-1, glycogen synthase kinase-3β, β-catenin, alkaline phosphatase, and osteocalcin were detected using enzyme- linked immunosorbent assay method. All patients were assessed in terms of erythrocyte sedimentation rate, C-reactive protein, Bath Ankylosing Spondylitis Disease Activity Index, Bath Ankylosing Spondylitis Functional Index, Ankylosing Spondylitis Disease Activity Score, and the modified Stoke’s Ankylosing Spondylitis Spine Score. Pearson’s correlation test was used to analyze the correlation between serum bone turnover markers and clinical assessment indexes. Results: No significant difference was observed between AS patients and healthy controls for the levels of glycogen synthase kinase-3β, β-catenin, alkaline phosphatase, and osteocalcin, respectively (p>0.05). The level of Dickkopf-1 was significantly higher in AS patients (1914.5±407.8 pg/mL) than in healthy controls (1729.1±352.9 pg/mL) (p<0.05). There was no correlation between high Dickkopf-1 level and any of the clinical parameters contributing to inflammation or bone formation. However, the correlation between osteocalcin and disease duration was significant in AS patients (r=0.323, p=0.034). Conclusion: Alteration of bone turnover markers in canonical wingless pathway was observed in AS. This might partially explain the complicated mechanism of bone formation in the disease.